2020
DOI: 10.3390/molecules25153484
|View full text |Cite
|
Sign up to set email alerts
|

Plant Natural Products for the Control of Aedes aegypti: The Main Vector of Important Arboviruses

Abstract: The mosquito species Aedes aegypti is one of the main vectors of arboviruses, including dengue, Zika and chikungunya. Considering the deficiency or absence of vaccines to prevent these diseases, vector control remains an important strategy. The use of plant natural product-based insecticides constitutes an alternative to chemical insecticides as they are degraded more easily and are less harmful to the environment, not to mention their lower toxicity to non-target insects. This review details plant species and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 142 publications
(329 reference statements)
0
73
0
11
Order By: Relevance
“…The use of curcumin, a natural PS extracted from the rhizomes of Curcuma longa plant, represents an ecologically positive alternative for vector control, since this molecule is already present in nature and can be easily degraded, being less harmful to the environment and non‐target organisms 17–19 . Some studies also showed that extracts and essential oils from Curcuma longa have larvicidal and repellent activity, 20,21 as well as isolated curcuminoids 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of curcumin, a natural PS extracted from the rhizomes of Curcuma longa plant, represents an ecologically positive alternative for vector control, since this molecule is already present in nature and can be easily degraded, being less harmful to the environment and non‐target organisms 17–19 . Some studies also showed that extracts and essential oils from Curcuma longa have larvicidal and repellent activity, 20,21 as well as isolated curcuminoids 22 .…”
Section: Introductionmentioning
confidence: 99%
“…These extracts or compounds belong to a large group of products termed ‘bioinsecticidals’ and could form part of an integrated approach for effective vector management. Distinct extracts were reported to show potent activities against the Aedes genus 34 . The M. acutifolium extract reported here demonstrated larvicidal properties with LC 50 205.39, 95.89 and 75.69 mg L –1 after 24, 48 and 72 h exposure, respectively.…”
Section: Discussionmentioning
confidence: 71%
“…The volatile oil of C. pubescens at the concentration used was inactive against Ae. aegypti larvae, according to the criteria described by Silvério et. al., (2020).…”
Section: Discussionmentioning
confidence: 99%
“…The results were analyzed using non-linear statistics (PROBIT), Statistica 12.0. The following criteria were used to assess larvicidal activity: lethal concentration 50 (LC50) ≤ 50 µg/mL is considered very active, LC50 between 50 and 100 µg/mL active, and LC50 ˃100 μg/mL inactive (Silvério, et al, 2020). It is a woody shrub, about 1.5 m tall in clump.…”
Section: Methodsmentioning
confidence: 99%